Praktik Usaha Kemitraan Ayam Potong dalam Perspektif Hukum Ekonomi Syariah di Desa Limansari - Prasetyo, Trinoto; Syukur, Iskandar; Santoso, Rudi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
This study examines the practice of broiler chicken farming partnership with PT. SBA in Limanasari Village from the perspective of Islamic economic law. This study uses qualitative research methods and field study approaches, with data collection through interviews, observations, and documentation from key informants. The results of the study indicate that the partnership model with PT. SBA is in accordance with Islamic economic principles, namely avoiding elements of usury, gharar, and maysir. This study also identified several positive outcomes from the partnership, including improving local economic conditions, improving farmer skills, and developing infrastructure. However, this study also highlights several potential weaknesses, such as the risk of creating economic dependency among the farmers involved. Overall, this study provides a comprehensive analysis of the benefits and limitations of the partnership model in the context of Islamic economic law.